Optimizing Principal Academic Supervision Through the SWOT Analysis Approach - Azimatul Af'idah; Nunuk Hariyati; Mohammad Syahidul Haq; Amrozi Khamidi; Nabila Dwi Wahyu Santoso (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to identify the inhibiting and supporting factors in the implementation of academic supervision by school principals using a SWOT analysis approach based on a literature review. Through a systematic literature review of various research sources related to academic supervision and communication in educational management, it was found that strengths such as principal competence, structured supervision with effective communication between principals and teachers, and facility support are the main assets for successful supervision. Meanwhile, weaknesses such as time constraints, limited resources, and a lack of innovation in supervision and communication approaches remain challenges. Opportunities arise from supportive education policies, technological advances that can strengthen internal communication, and the role of active learning communities in sharing information and collaboration. However, threats such as dynamic policy changes and resistance to change require adaptive supervision strategies, open communication, and collaboration in order to optimize academic supervision. The results of this study provide an overview of strategies for school principals and policy makers to optimize academic supervision through effective communication approaches in order to improve teacher professionalism and the quality of learning in schools.